Simultaneous analysis of derivatized allyl isothiocyanate together with its phase II metabolites by ultra‐high‐performance liquid chromatography/tandem mass spectrometry. (16th February 2022) - Ngan, Hiu‐Lok; Wang, Tao; Ru, Yi; Chen, Yanyan; Li, Charlie; Cai, Zongwei
Abstract : Rationale: Allyl isothiocyanate (AITC) in food products such as wasabi is commonly analyzed by gas chromatography/mass spectrometry (GC/MS), while liquid chromatography/mass spectrometry (LC/MS) is more suitable for the polar metabolites. The development of an effective method for the simultaneous determination of AITC and its phase II metabolites is needed to support drug metabolism and pharmacokinetics (DMPK) studies. Methods: Derivatization of AITC by reaction with N ‐( tert ‐butoxycarbonyl)‐L‐cysteine methyl ester ( t BocCysME) was used for ultra‐high‐performance liquid chromatography/electrospray ionization mass spectrometry (UHPLC/ESI‐MS) analysis, allowing the simultaneous determination with its phase II metabolites. At room temperature, reaction conditions have been optimized to maximize the reaction of AITC with t BocCysME quantitively. Reaction selectivity was examined by the presence of AITC metabolites. Quantification of AITC was performed by multiple reaction monitoring (MRM) with an external calibration method and applied on the serum of C57BL/6 J mouse for a DMPK study. Results: The limit of quantification (LOQ) was determined to be 0.842 nM from the derivatization method and by UHPLC/MS/MS analysis. The method accuracy in the mouse serum samples was 75 ± 2% with a relative standard deviation (RSD) of 3.0% of method variation. The UHPLC/MS/MS analysis gave RSDs of 0.2% and 1.8% for intra‐day and inter‐day variations. With the newly developed method, AITC could be detected in mouse serum upon oral administration for the first time. Conclusions: An analytical method involving a rapid derivatization pre‐treatment and quantitative UHPLC/ESI‐QqQ‐MS/MS analysis has been developed for a biological sample assay of AITC, enabling selective and sensitive detection of the AITC derivative and AITC metabolites simultaneously. The method developed could be applied to the DMPK study of AITC as well.